البحث عن الجودة في نظام الـLMD "آليات التطبيق وسبل التعزيز" - يونس, سميحة (Sciences humaines, 2014)
تتناول هذه الدراسة موضوعاً نال اهتمام الكثير من التربويين والقائمين على مؤسسات التعليم بشكل عام، ومؤسسات التعليم الجامعي بشكل خاص، حيث استهدفت هذه الدراسة تحديد مفهوم الجودة وكل ما يتعلق به من مفاهيم، كما حاولت البحث عن الجودة في نظام الـ LMD المطبق في الجزائر.   This study is dealing with a subject, which attained more interest from educational specialists. It aimed at identifying “Quality concept” of the educational institutions, and determining the reasons and the requirements of the application of quality in higher education. Where this study aimed to define the concept of quality and everything related to its concepts, as you try to search for quality in the LMD system applied in Algeria.